2021
DOI: 10.1530/raf-21-0044
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective cohort study on preparation regimens for frozen embryo transfer

Abstract: Objective: To examine the pregnancy outcomes from frozen embryo transfer (FET) cycles using different endometrial preparation regimens, compared to ovulation induction with letrozole (letrozole OI). Design: Retrospective cohort study. Setting: Fertility centre in Sydney, Australia. Patient(s): 6060 frozen embryo transfer cycles. Interventions: Cycles were stratified into one of four ways to achieve endometrial preparation. These were either a natural, letrozole OI, OI with follicle stimulating hormone (FSH OI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
2
0
2
Order By: Relevance
“…Lastly, after adjustments to the timing of FET were made for patients found to be pre-receptive or post-receptive, there was a pregnancy rate of 33.3%, which is comparable to the 35.2% pregnancy rate of the control group. Several studies have also indicated a clinical pregnancy rate of about 34% for non-ERA FET, thus showing this to be similar to the findings in the literature [64,65]. Since the pregnancy rates were comparable in both the control and ERA groups, the study concluded that having patients undergo ERA testing before FET shows no improvement in pregnancy rates in patients with zero or some implantation failures.…”
Section: Clinical Outcomes Using Era In Infertile Womensupporting
confidence: 83%
“…Lastly, after adjustments to the timing of FET were made for patients found to be pre-receptive or post-receptive, there was a pregnancy rate of 33.3%, which is comparable to the 35.2% pregnancy rate of the control group. Several studies have also indicated a clinical pregnancy rate of about 34% for non-ERA FET, thus showing this to be similar to the findings in the literature [64,65]. Since the pregnancy rates were comparable in both the control and ERA groups, the study concluded that having patients undergo ERA testing before FET shows no improvement in pregnancy rates in patients with zero or some implantation failures.…”
Section: Clinical Outcomes Using Era In Infertile Womensupporting
confidence: 83%
“…Previous studies indicate lower risk of hypertensive disorders in pregnancies with no endometrial preparation (natural cycles),( 39 ) but similar risks of both stillbirth and neonatal death in pregnancies conceived in natural, programmed and stimulated frozen-ET cycles. ( 40 ) ( 39 )…”
Section: Discussionmentioning
confidence: 99%
“…We had no data on endometrial preparation in frozen-ET. Previous studies indicate low risk of hypertensive disorders in pregnancies with no endometrial preparation (natural cycles) (39), but similar risks of both stillbirth and neonatal death in pregnancies conceived in natural, programmed, and stimulated frozen-ET cycles (39,40) Implications Despite the high risk of adverse perinatal outcomes in ART pregnancies, including preterm birth, low birth weight, and placental complications as shown previously in this study population (18,29,41), we found no increased risk of stillbirth in ART-conceived pregnancies. In contrast, neonatal mortality was higher after both fresh and frozen-ET compared with singletons conceived without medical assistance; however, the high risk attenuated in analyses according to the gestational age.…”
Section: Comparisons To Other Studiesmentioning
confidence: 94%
“…Пероральный прием эстрогенов может предрасполагать к образованию камней в желчном пузыре в связи со снижением синтеза желчных кислот. Кроме того, повышение уровня эстрона может способствовать увеличению коэффициента насыщения желчи и, следовательно, снижению растворимости желчных кислот [8][9][10][11][12][13][14].…”
Section: Discussionunclassified
“…Трансдермальное нанесение эстрадиола на кожу обеспечивает постепенное прогредиентное поступление активного вещества в кровоток, что поддерживает относительно постоянную концентрацию без сильно выраженных пиков. Более физиологичное соотношение эстрадиола и эстрона наблюдается при трансдермальном применении, что более точно воспроизводит ситуацию, характерную для яичникового цикла[8][9][10][11][12][13][14].Изучены фармакокинетические параметры разных препаратов эстрогенового ряда в форме пластыря, геля, таблеток. Абсорбция геля (17β-эстрадиола) в дозе 1 г сопоставима с одной таблеткой эстрадиола валерата 2 мг.…”
unclassified